AUDIT OF INCOME FROM LOCAL FEES IN SELECTED COMMUNES OF THE POMERANIAN PROVINCE IN POLAND - Cezary Szydłowski (Polityki Europejskie, Finanse i Marketing)
The article presents the importance of auditing the assessment of a commune's budget revenues for tourist fees (local fee or spa fee) as a tool enabling its increase by the commune authorized to impose it. The purpose of this article is to present on the basis of selected coastal municipalities of the Pomeranian Voivodeship in Poland, the role and significance of the audit of the assessment of income to the municipal budget in terms of local and spa fees. The article uses case study, analytical method, inference method and document examination method as the research methodology. The source materials for the analysis were documents made available on the pages of the Public Information Bulletin by the assessed local government units from the Pomeranian Voivodeship (reports on the implementation of the budget and Rb-27s reports containing information on revenue for the year). The local and spa fees constitute a small share in the total income of the budgets of the surveyed municipalities. The key factor improving the revenues of municipalities from local and spa fees is the improvement of their collection system. The risk of inefficient collection of fees by those who collect them from tourists is a threat to effective collection of the fees. Therefore, individual communes should improve the supervision system and control of toll collection by hotel service providers.